Pengaruh Pendidikan Dan Pelatihan, Lingkungan Kerja Dan Motivasi Terhadap Kepuasan Kerja Karyawan Pt Misaja Mitra Pati - Hardiana, Netty; , Ir. Irmawati, S.E., M.Si (2015)
Job satisfaction is the desire and expectation that has been reached in a person to the extent to which individuals feel positively or negatively on the various factors of the tasks in the job. Several indicators such as education and training, work environment and motivation is an attempt by the company to achieve the level of employee satisfaction. This study aims to examine and analyze the influence of education and training, work environment and motivation as well as the most dominant variable effect on job satisfaction of employee PT Mitra Misaja Pati. Based on this study is expected to be taken into consideration in decision making, human resource management to improve employee job satisfaction. This research was conducted using primary data with a total sample of 100 employees of a total population of 425 who work in PT Mitra Misaja Pati. The analytical method used is validity, reliability, determination, t test, F test, the classic assumption test and multiple linear regression analysis. Based on the results of this research note that the results of multiple linear regression is Y = 6161 + 0270 (X1) + 0.614 (X2) + 0649 (X3), where education and training (X1), work environment (X2), and motivation (X3) has a significant positive effect on employee satisfaction (Y). Then the results of the third test variable T has a significant positive effect on employee satisfaction (2.986 (X1), 3,831 (X2), 3315 (X3)> 1.985). Taken together the F test are significant positive effect on job satisfaction (75 908> 2.70). R-square test results give a value of 0703, which means 70.3% variable job satisfaction can be explained by the three independent variables, while the remaining 29.7% can be explained by other variables outside the three variables used in this study.